Effect of inspiratory muscle training on hypoxemia in obese patients undergoing painless gastroscopy: protocol for a single-center, double-blind, randomized controlled trial - Yan, Lijuan; Wang, Xiao; Du, Kairong; Liang, Ying (Frontiers in Medicine, 2023)
Introduction: Obese patients who undergo painless gastroscopy are particularly prone to suffer from upper airway obstruction, respiratory depression, and subsequent hypoxemia. Despite adequate preoxygenation, the incidence of hypoxemia remains high. Recently, inspiratory muscle training (IMT) has been considered to be a promising strategy to increase respiratory muscle strength and endurance with the attendant improvement of pulmonary function. However, it remains unclear whether IMT is associated with a lower rate of hypoxemia in obese patients during this sedative procedure. This study aims to investigate the effectiveness of IMT used in obese patients who are scheduled for selective painless gastroscopy. Methods and Analysis: This prospective, controlled randomized clinical trial (RCT) will enroll 232 obese patients with a body mass index (BMI) of 35-39.9 kg·m-2 who undergo painless gastroscopy at the First Affiliated Hospital of Xiamen University. Subjects will be randomly assigned to two groups with a 1:1 ratio. Participants in both groups will receive IMT for 4 weeks prior to gastroscopy. The intervention group will receive IMT with a load of 30% of the maximal inspiratory pressure (Pi(max)) in the first week, with an increase of 10% per week since the following week, while the counterparts in the control group will not receive any load during the 4-week IMT. The primary outcome is the incidence of hypoxemia during painless gastroscopy. Secondary outcomes include the need for airway maneuvers, blood pressure changes, sleep quality assessment, pro-inflammatory cytokines levels, and monitoring of adverse events. Discussions: The outcomes of this study will offer invaluable guidance for the clinical implementation of IMT as a potential non-invasive preventive measure. Additionally, it stands to enrich our comprehension of anesthesia management and airway-related challenges in obese patients undergoing procedural sedation, which we anticipate will further contribute to addressing the turnaround concerns within high-volume, swiftly paced ambulatory endoscopy centers. Ethics and Dissemination: This study has been approved by the Ethics Committee of the First Affiliated Hospital of Xiamen University (2022, No.091). The results will be submitted for publication in peer-reviewed journals. Trial Registration Number: This trial has been registered with the China Clinical Trial Center (ChiCTR2200067041) on December 26, 2022.